2015
DOI: 10.1007/s00384-015-2303-x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of ultra-low anterior resection combined with or without intersphincteric resection in lower rectal cancer patients

Abstract: Compared with uLAR without ISR, the transabdominal ISR with levator-sphincter reinforcement provides a safe resection plane with competent CRM, concurrently reduces substantial complications, and marginally promotes recovery of neorectal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…However, advancements in surgical techniques such as ultra-low anterior resection and intersphincteric resection (ISR), enabled patients with low rectal cancer to undergo surgery without sacrificing the anal sphincter. [ 1 3 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, advancements in surgical techniques such as ultra-low anterior resection and intersphincteric resection (ISR), enabled patients with low rectal cancer to undergo surgery without sacrificing the anal sphincter. [ 1 3 ]…”
Section: Introductionmentioning
confidence: 99%
“…When SSR is performed for very low rectal tumors that are close to the anal sphincter complex, the distal boundary of the resection is located in the anal canal. While small-scale studies have shown ISR to be generally safe, [ 3 , 11 , 12 ] the oncological safety profile of the resection of very low rectal tumors with ambiguous external anal sphincter involvement and uncertain circumferential resection margin (CRM) remains unclear. Moreover, the clinicopathological heterogeneity of patients renders it difficult to interpret the currently published data.…”
Section: Introductionmentioning
confidence: 99%
“…There is an ongoing intense activity in risk factor research regarding outcomes of visceral surgery which needs to be methodologically channeled and implemented in clinical decision making [30][31][32].…”
Section: Examplesmentioning
confidence: 99%
“…Of these factors, sphincter dysfunction has been focused on as the main cause. The external anal sphincter (EAS), internal anal sphincter (IAS), and puborectalis muscle (PM) essentially establish continence [5] [7] [8]. Among these sphincter muscles, EAS is the most important to prevent FI [5] [7] [8].…”
Section: Introductionmentioning
confidence: 99%
“…The external anal sphincter (EAS), internal anal sphincter (IAS), and puborectalis muscle (PM) essentially establish continence [5] [7] [8]. Among these sphincter muscles, EAS is the most important to prevent FI [5] [7] [8]. Especially, voluntary contractions of EAS prevent FI that may be induced by an increase in abdominal pressure due to coughing or postural changes [7] [8].…”
Section: Introductionmentioning
confidence: 99%